2000
DOI: 10.1055/s-2000-9426
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Transport of Bile Salts

Abstract: The vectorial secretion of bile salts from blood into bile is a major driving force for bile formation. The basolateral hepatocyte membrane extracts bile salts from sinusoidal blood via Na(+)-dependent and Na(+)-independent membrane transporters. Na(+)-dependent uptake of bile salts is mediated by the Na(+)-taurocholate co-transporting polypeptide, a 51-kDa protein that is exclusively expressed in hepatocytes. Na(+)-independent uptake of bile salts is mediated by the organic anion transporting polypeptides, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
163
1
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(172 citation statements)
references
References 239 publications
(219 reference statements)
2
163
1
6
Order By: Relevance
“…25 Although Ntcp expression was normal in the livers of P0 PEX2 Ϫ/Ϫ mice (not shown), protein expression was significantly reduced in P10 untreated mutants and was further decreased with BA feeding (Fig. 10A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Although Ntcp expression was normal in the livers of P0 PEX2 Ϫ/Ϫ mice (not shown), protein expression was significantly reduced in P10 untreated mutants and was further decreased with BA feeding (Fig. 10A).…”
Section: Resultsmentioning
confidence: 99%
“…25 Northern blot analysis revealed that by P36 the major Oatp1 transporter was expressed in control mice but not in BA-fed PEX2 mutants (Fig. 12).…”
Section: Resultsmentioning
confidence: 99%
“…A major driving force for bile formation is active secretion of bile salts, mediated by the adenosine triphosphate-dependent bile salt export pump, ABCB11. 16 Bile salt excretion induces an osmotic gradient that in turn causes the flow of water and accompanying solutes into the bile canalicular lumen. [17][18][19] Bile salts have detergent properties that enable them to solubilize membrane lipids and are present in millimolar concentrations in the canalicular lumen.…”
mentioning
confidence: 99%
“…Recent studies have described some of the genes involved in these transport processes; however, it is clear that many other genes and gene products remain to be identified and characterized (1)(2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%